Women and Extremism: A Feminist Analysis of European Female ISIS Recruits - Mahmudah, Sarah Hajar (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2023)
This study investigates the active participation of European women, particularly British citizens, in ISIS's operations and propaganda, which challenges traditional gender norms and perceptions of Muslim women in Western societies. The research used postmodern feminist theory to delve into the multifaceted motivations driving these women—from feelings of alienation and promises of empowerment to ideological aspirations—and examines their roles as recruiters, propagandists, and enforcers within the al-Khansaa Brigade. Specific cases, such as Aqsa Mahmood, illustrate the strategic use of social media to romanticize life in the caliphate while simultaneously exploiting women through constructs like